(untitled) (Journal of Medicine, 2014)
Amegakaryocytic thrombocytopenia is a rare variety of bone marrow aplasia characterized by thrombocytopenia in association with markedly diminished bone marrow megakaryocytes. It can occur as a component of aplastic anaemia or as an isolated form. Here we report a case of a teenage girl presented with bleeding per vagina and generalized weakness which is diagnosed as a case of amegakaryocytic thrombocytopenia by bone marrow examination. It will evolve into aplastic anaemia with the course of the disease. DOI: http://dx.doi.org/10.3329/jom.v14i2.19690 J Medicine 2013, 14(2): 207-209